THE ROLE OF THE CONNECTIVE TISSUE GROUND SUBSTANCES (MUCOPOLYSACCHARIDES) IN ALLERGIC INJURY - Rinehart, James F. (1951)
The basic histologic reactions of the classic allergic diseases and of several systemic diseases in which allergic mechanisms appear to operate are described and illustrated. Particular attention is drawn to the ground substances—mucopolysaccharides—which constitute important elements of connective tissue and vascular structure. The intimate locus of the allergic reaction appears to be in and to involve a swelling of such substances. It is suggested that antibodies (and possibly antigens) may be attached to these mucinous ground substances of the connective tissues.